Kajian Feminisme terhadap Novel I Am Malala (The Girl Who Stood Up for Education and Was Shot By The Taliban) Karya Malala Yousafzai dan Christina Lamb - Nur Syamsiah (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The purpose of this study was to reveal the literary in the novel I am Malala by Malala Yousafzai and Cristina Lamb, from the viewpoint of feminism which includes; The position of women, Pro-feminism and Cons of feminism in the novel I am Malala by Malala Yousafzai and Cristina Lamb. This study is a qualitative study using descriptive method, since the data in this study in the form of words, and sentences instead of the numbers as a result of statistical calculations. In addition, research reports will contain excerpts of data to provide an overview description of the report. Data were derived from the text of the novel, that is, the quote in the form of words, phrases, sentences, sentence quote form narrative or dialogue. From the data analysis, it can be concluded that awareness of equality which is owned by men and women, both within the family and community environment. In the novel I am Malala by Malala Yousafzai and Christina Lamb showed that aura feminist actualized in the form of a daughter who struggle to survive even though three bullets had claimed smile and fighting for and campaigning for the right to education for girls.